Happiness, well being and work: a possible encounter in a managerial perspective? - Gomes, Maria Helena Scalabrin Cardoso; Barcaui, André Baptista; Limongi-França, Ana Cristina; Bresciani, Luis Paulo; Correa, Sueli (Revista de Administração da UFSM, 2019)
This article starts from the examination of the historical conceptions of work and its meaning in the life of organization managers. As the interest in work, well-being and happiness increase, also increase in the same proportion the need to elaborate an appropriate taxonomy of these concepts, starting from its meaning and characteristics attributed to the work. These scores help to determine how work juxtaposes the happiness and well-being constructs. A taxonomy and its indicators help determine how juxtaposes the happiness and well being constructs. Subsidizing the theoretical studies, a field research was done with 249 executive managers of the Rio-São Paulo axis. The statistical treatment adopted was an exploratory factorial analysis. The research finds revealed that the pace of activity imposed on managers is closed to the original meaning of the term, suffering. It is assessed - not generalizable - that happiness, well-being and quality of life at work, are not isolated constructs, but are aligned with the aspirations of the executives, understanding that, in order to have life outside of work, there must be life in it.